Serum Uric Acid Concentrations in Meat Eaters, Fish Eaters, Vegetarians and Vegans: A Cross-Sectional Analysis in the EPIC-Oxford Cohort - Schmidt, Julie A. (Public Library of Science, 2013)
INTRODUCTION: Circulating concentrations of uric acid may be affected by dietary components such as meat, fish and dairy products, but only a few studies have compared uric acid concentrations among individuals who exclude some or all of these foods from their diet. The aim of this study was to investigate differences in serum uric acid concentrations between meat eaters, fish eaters, vegetarians and vegans. SUBJECTS AND METHODS: A sample of 670 men and 1,023 women (424 meat eaters, 425 fish eaters, 422 vegetarians and 422 vegans, matched on age and sex) from the European Prospective Investigation into Cancer and Nutrition Oxford cohort were included in this cross-sectional analysis. Diet was assessed using a semi-quantitative food frequency questionnaire and serum concentrations of uric acid were measured. Mean concentrations of uric acid by diet group were calculated after adjusting for age, body mass index, calcium and alcohol intake. RESULTS: In both men and women, serum uric acid concentrations differed significantly by diet group (p<0.0001 and p = 0.01, respectively). The differences between diet groups were most pronounced in men; vegans had the highest concentration (340, 95% confidence interval 329–351 µmol/l), followed by meat eaters (315, 306–324 µmol/l), fish eaters (309, 300–318 µmol/l) and vegetarians (303, 294–312 µmol/l). In women, serum uric acid concentrations were slightly higher in vegans (241, 234–247 µmol/l) than in meat eaters (237, 231–242 µmol/l) and lower in vegetarians (230, 224–236 µmol/l) and fish eaters (227, 221–233 µmol/l). CONCLUSION: Individuals consuming a vegan diet had the highest serum concentrations of uric acid compared to meat eaters, fish eaters and vegetarians, especially in men. Vegetarians and individuals who eat fish but not meat had the lowest concentrations of serum uric acid.